Nonlinear dynamics of a dense two-dimensional dipolar exciton gas - Rapaport, R; Chen, G; Simon, S (2006)
We use a simple model to describe the nonlinear dynamics of a dense two-dimensional dipolar exciton gas. The model predicts an initial fast expansion due to effective dipole pressure, followed by a much slower diffusion. The model is in very good agreement with recent experimental results. We show that the dipole-pressure-induced expansion strongly constrains the time available for achieving and observing Bose-Einstein quantum statistical effects, indicating a need for spatial exciton traps. We also suggest that nonlinear ballistic exciton transport due to the strong internal dipole pressure is readily achievable. © 2006 The American Physical Society.